How Can We Overcome the Challenges of Providing School-Based Fluency Services? - Chmela, Kristin; Johnson, Laura (Seminars in Speech and Language, 2018)
Providing speech and language services in the school setting can be challenging, especially for complex problems such as stuttering and other fluency disorders. Speech–language pathologists (SLPs) feel less comfortable working with students who have fluency disorders, which makes problem solving around delivering these services even more difficult. The purpose of this article is to identify three categories of challenges school-based therapists may face when evaluating and treating this population. The challenges discussed in this article are drawn from our literature, interviews with several practicing therapists, and the authors' experiences providing assessment and therapy to school-age children, as well as consultations and in-services for school-based SLPs. We provide suggestions for facilitating positive change across these challenges.
Keywords: Stuttering; fluency disorders; school speech–language pathologists; school setting; challenges